WATER QUALITY AND AQUACULTURE: AN ASSESSMENT OF THE SUITABILITY OF OGIDEKPE RIVER FOR AQUACULTURE - Egun, Nkonyeasua Kingsley; Edoreh, James; Olowo, Ukpamufo Cyril; Oboh, Ijeoma Patience (FUDMA Journal of Sciences, 2025)
The success of aquaculture depends on the quality of its water source. The increasing practice and establishment of earthen ponds for aquaculture in close proximity to lotic water bodies has necessitated the need for the suitability assessment of their water quality. The aim of this study is to ascertain the suitability of Ogidekpe River as source of water for aquaculture practice. Water samples were collected from four (4) designated stations along the Ogidekpe River from September 2023 to February 2024 and twenty (20) physico-chemical parameters were analyzed according to standard methods. Observed concentration values were compared with the Nigerian Standard Water Quality Criteria for Fisheries. Concentrations of physico-chemical parameters were within their respective permissible limits, except for turbidity (27 – 30.6 NTU), dissolved oxygen (3.06 – 5.06 mg/L), iron (0.33 – 0.39 mg/L), chromium (0.04 – 0.08 mg/L), lead (0.01 – 0.013 mg/L) and zinc (0.21 – 0.38 mg/L) at all the stations. High water turbidity and heavy metal – iron, chromium, lead and zinc content values which exceeded the water quality criteria for fisheries, makes the river an unsuitable water source for aquaculture. Utilizing the River as source of water for aquaculture requires that water retention ponds be constructed to allow for sedimentation and treatment before use for fish culture. There is need also to identify point sources of pollution within the watershed and enforce compliance to environmental laws in order to improve the overall water quality of the river.